Is Porcine Small Intestinal Submucosal Extracellular Matrix (ECM) a Suitable Material for Right Ventricular Outflow Tract Reconstruction in Association With Pulmonary Valve Replacement?. Issue 4 (July 2022) - Burke, Christopher R.; Lewis, Erik; Schreiter, Nicholas A.; Bartlett, Heather; Krieger, Eric V.; Anagnostopoulos, Petros V.; Verrier, Edward D.; Hermsen, Joshua L.
Pulmonary valve replacement (PVR) with right ventricular outflow tract (RVOT) reconstruction is a common congenital cardiac operation. Porcine submucosal intestinal-derived extracellular matrix (ECM) patches have been used for RVOT reconstruction. We present 2 adult patients with Tetralogy of Fallot who underwent PVR with RVOT reconstruction utilizing ECM. Both cases required reoperation due to patch dehiscence causing a large paravalvular leak. One patient also had a pseudoaneurysm associated with ECM dehiscence. There may be a propensity for ECM dehiscence in this application and, based on these cases, we recommend avoidance of ECM in RVOT reconstruction with PVR. PVR patients repaired with ECM should be monitored for this complication.